IL-13 Impairs Tight Junctions in Airway Epithelia - Hanna Schmidt (International Journal of Molecular Sciences, 2019)
Interleukin-13 (IL-13) drives symptoms in asthma with high levels of T-helper type 2 cells (Th2-cells). Since tight junctions (TJ) constitute the epithelial diffusion barrier, we investigated the effect of IL-13 on TJ in human tracheal epithelial cells. We observed that IL-13 increases paracellular permeability, changes claudin expression pattern and induces intracellular aggregation of the TJ proteins zonlua occludens protein 1, as well as claudins. Furthermore, IL-13 treatment increases expression of ubiquitin conjugating E2 enzyme UBE2Z. Co-localization and proximity ligation assays further showed that ubiquitin and the proteasomal marker PSMA5 co-localize with TJ proteins in IL-13 treated cells, showing that TJ proteins are ubiquitinated following IL-13 exposure. UBE2Z upregulation occurs within the first day after IL-13 exposure. Proteasomal aggregation of ubiquitinated TJ proteins starts three days after IL-13 exposure and transepithelial electrical resistance (TEER) decrease follows the time course of TJ-protein aggregation. Inhibition of JAK/STAT signaling abolishes IL-13 induced effects. Our data suggest that that IL-13 induces ubiquitination and proteasomal aggregation of TJ proteins via JAK/STAT dependent expression of UBE2Z, resulting in opening of TJs. This may contribute to barrier disturbances in pulmonary epithelia and lung damage of patients with inflammatory lung diseases.